GAMBARAN FAKTOR RISIKO KELUHAN LOW BACK PAIN PADA PEKERJA PORTER CARGO BANDARA - Mila, Silvia Yopi Putri; Saputra, Adi; Sutarsa, I Nyoman (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Porters as manual handling workers use a lot of physical strength as a foundation in carrying out the work of lifting and transporting goods. A complaint that many porters may experience is low back pain. Low back pain is a disease that causes pain in the lower back, such as the waist, hips, buttocks and legs. This study aims to describe the risk factors that influence low back pain complaints in porter cargo based on sociodemographic characteristics, occupational factors, and the environment. This research is a quantitative observational study with a cross-sectional descriptive approach. This research was conducted at Ngurah Rai International Airport Cargo with a total sample of 34 respondents. The research sample is porter cargo workers in the Regulated Agent (RA) division. The sampling technique was carried out using total sampling with a mixture of inclusions and exclusions. Data collection techniques were carried out using questionnaires, microtoise, weight scales, and cameras. Data were analyzed using descriptive frequency test and cross tabulation using SPSS. The results showed that most of the airport cargo porter workers complained of severe LBP aged >35 years (61.8%) and working experience of >5 years, were active smokers, normal body mass index, had a very high risk work attitude and moderate stress. The conclusion of this study was that most of the airport cargo porter workers experienced severe LBP complaints (70.6%) with a very high average work attitude. As an effort to maintain the productivity of airport porter cargo workers, companies can provide routine health checks for workers at least once or every three months for early health checks. Keywords: Low Back Pain Complaints, Porter, Airport, REBA.